Comparison of socio economic and demographic characteristics of HIV and HIV-infected tuberculosis patients in Kota Bharu Hospital, Kelantan - Narwani Hussin; Naing, Nyi Nyi (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Tuberculosis (TB) is a significant cause of morbidity and mortality in HIV infected patients. There are many potential factors in HIVpatients that influence them in high risk of contracting TB. The aim of this analysis was to compare the socio economic and demographic characteristics of HIV and HIV infected TB patients in Kota Bharu Hospital, Kelantan. This was a case control study on 97 HIV (control) and 97 HIV infected TB (case) patients. An interviewer guided questionnaire and review of medical record were done to gather the information. For controls, majorities were females (62.9%), Malays (83.5%), married (46.4%), Malaysian (94.8%) with a mean age of 32.34 Y8.0 years. 83.5% of them completed their secondary school or tertiary education and 67.0% were from non-professional working group. About 56% of patients fell in the poverty group and the family member to room ratio was 2.4. For cases, majorities were males (83.5%), Malays (74.2%), single (48.5%), Malaysian (96.9%) with a mean age of 36.0 + 8.4 years. 78.4% completed their secondary school or tertiary education and 73.2% were from non-professional working group. The "above poverty and below average" monthly household income group contributed of 45.4% of all patients. The family member to room ratio was 1.9. The significant difference between cases and control were found in age, family member to room ratio, sex and marital status. As a conclusion, the differences in those characteristics should be considered in assessing a risk of contracting TB in patients with HIV infection.